Acessibilidade às pessoas com deficiência física nas unidades de saúde da atenção primária no estado de Goiás - Mamed, Samira Nascimento (2016)
Introduction: Accessibility for disabled people at primary healthcare units has a fundamental role in the use of health services, as well as the organization of health services targeted at this population, since there is an impressive number of disabled people in the state of Goiás and in Brazil in general. Objective: To analyze accessibility of disabled people to primary healthcare services in the state of Goiás. Method: A descriptive cross-sectional study was conducted with secondary data from an external evaluation of the National Program for Improvement of Access and Primary Healthcare Quality (PMAQ-AB, as per its acronym in Portuguese). The study was developed in all 246 cities of Goiás. The sample was made up of 1,216 healthcare units and 677 healthcare professionals in the cycle 1 of PMAQ-AB; and 975 healthcare units and 1,180 healthcare professionals in the cycle 2 of PMAQ-AB. Data were collected between June and August 2012 in the cycle 1 and from January to March 2014 in the cycle 2. The variables were analyzed descriptively and presented by means of absolute numbers, frequencies and means. Results: Only 30% to 40% of the studied healthcare units had sidewalks, floors and ramps accessible to disabled people. Between 20% and 35% of the healthcare units had adapted doors and hallways, except for units in cities with up to 50,000 inhabitants in cycle 2, which accounted for almost 50% of the units with these elements. Regarding adapted restrooms, less than 20% of the healthcare units in cycle 1 had them, whereas between 20% and 55% of the units in cycle 2 presented this feature. As for the organization of healthcare services toward disabled people, almost 95% of the teams defined the coverage area, however only half of them had records on the number of cases of disabled people. Conclusion: Primary healthcare units and services in the state of Goiás are not structured in terms of accessibility to disabled people, which makes the delivery of care to this population poor. In this sense, there is a clear need for investments on the part of health managers and professionals for continuing education and financial resources to adapt these units and qualify healthcare teams to provide universal, comprehensive and humanized health care to disabled people.